Sacred violence or strategic faith? Disentangling the relationship between religion and violence in armed conflict. (March 2016) - Isaacs, Matthew
Why are religious conflicts more violent than non-religious conflicts? Research has argued that religion pushes partisans toward violence. However, existing research suffers from widespread problems of measurement validity and fails to confront the possibility of endogeneity in the relationship between religion and violence. This article develops a more precise measure of the relevance of religion to conflict based on the use of religious rhetoric by political organizations. With this approach in mind, this article disentangles the causal sequence linking religious rhetoric and violence using annually coded data on the rhetoric of 495 organizations worldwide from 1970 through 2012. The analysis finds a strong general correlation between religious rhetoric and violence. However, past use of religious rhetoric does not increase the likelihood that an organization will participate in violence or the overall intensity of conflict. On the contrary, previous participation in violence makes an organization more likely to adopt religious rhetoric for mobilization. Indeed, religious rhetoric becomes more likely as violence increases in intensity and conflict continues for longer periods of time. These findings suggest that violent actors adopt religious rhetoric to solve the logistical challenges associated with violence, including access to mobilizing resources and recruitment and retention of members. This article contributes to the study of religious conflict by providing evidence of endogeneity in the relationship between religion and violence and highlighting the need for temporally sensitive measures of religious mobilization.